Validation of the Oral Hygiene Habits Scale: Relationships with sociodemographic variables in the general and clinical population of Monterrey, Mexico. - Norma Rodríguez; José Moral (Universidad de Concepción., 2016)
Several socioeconomic factors are associated with poor oral hygiene habits. A version of the Oral Hygiene Habits Scale (OHHS) was developed in Mexico to measure these factors; however, its relationship with sociodemographic variables has not been studied. The verification of these relationships could contribute to the validation of the scale. Objective: To evaluate the relationship between oral hygiene habits and sociodemographic variables of sex, age, schooling, self-defined socioeconomic stratum, occupation and marital status in the general and clinical population of Monterrey, Mexico. Materials and Methods: A general population sample (GPS) of 256 participants and a clinical sample (CPS) of 240 participants were studied. The OHHS consisted of an eight-item Likert scale of 4 points ranging from 0 to 4. A descriptive correlational study was performed with a cross-sectional design. Data were analyzed using the Mann-Whitney U test, Kruskal-Wallis test, Spearman correlation coefficient, Cramer's V coefficient, and multivariate aligned rank test. Results: In GPS and CPS groups, OHHS was related to sex, schooling, socioeconomic stratum, occupation and marital status, but not to age. There were no significant interactions between the samples (GPS and CPS) and sociodemographic variables. Conclusion: There is a statistically significant relationship between oral hygiene habits and some sociodemographic variables in the general and clinical population. This relationship supports the validity of the OHHS.